Optimizing portfolio performance in the Philippine financial markets using smart-beta - Lauzon, Rosel Delmo (Animo Repository, 2022)
This study attempts to determine the impact of smart-beta strategies in portfolio optimization. In view thereof, five (5) zero-weighted and five (5) 100%-weighted smart-beta portfolios were constructed using: (a) fundamental indexation; (b) market capitalization weighting; and (c) minimum-variance optimization applying quadratic programming and cardinality-constraint. In conducting data analysis and review of the performance of the constructed smart-beta portfolios, Wilcoxon Sign Rank test, Chow’s test, Sharpe’s ratio, Treynor’s measure and Jensen’s index were conducted using the software R (version 4.1.1). Results show that while majority of the constructed smart-beta portfolios failed to reject the null hypothesis of obtaining annual returns with no significant difference against the market, three (3) out of 10 portfolios significantly outperform the market in terms of cumulative returns, Sharpe’s ratio and Jensen’s index. With reference to the derived betas and Treynor’s measure, the 10 smart-beta portfolios show inverse relationship with the market implying that these portfolios also serve as good alternatives in times of adverse market conditions. Keywords: Smart-Beta Strategy, Fundamental Indexation, Minimum-Variance Optimization, Cardinality-Constrained Minimum-Variance Optimization